Health and human rights of women imprisoned in Zambia - Todrys Katherine W; Amon Joseph J (BMC, 2011)
Abstract Background The healthcare needs and general experience of women in detention in sub-Saharan Africa are rarely studied and poorly understood. Methods A mixed-methods study was conducted including in-depth interviews with 38 adult female prisoners and 21 prison officers in four Zambian prisons to assess the health and human rights concerns of female detainees. Key informant interviews with 46 officials from government and non-governmental organizations and a legal and policy review were also conducted. Results Despite special protection under international and regional law, incarcerated women's health needs-including prenatal care, prevention of mother-to-child transmission of HIV, and nutritional support during pregnancy and breastfeeding-are not being adequately met in Zambian prisons. Women are underserved by general healthcare programs including those offering tuberculosis and HIV testing, and reported physical and sexual abuse conducted by police and prison officers that could amount to torture under international law. Conclusions There is an urgent need for women's healthcare services to be expanded, and for general prison health campaigns, including HIV and tuberculosis testing and treatment, to ensure the inclusion of female inmates. Abuses against women in Zambian police and prison custody, which violate their rights and compromise their health, must be halted immediately.